Analysis of the Role of School and Parent Partnerships on Children’s Social Emotional Development (Case Study at PAUD Al-Hidayah. Desa Bug-Bug, Lombok Barat) - Herlina, Herlina; Zulfakar, Zulfakar; Sulastri, Ni Made (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Children’s social and emotional development is an important aspect that influences their well-being and future success. Children who have good social and emotional skills are able to interact well with others, manage their emotions healthily, and demonstrate positive behavior. In the context of early childhood education, such as in PAUD (Early Childhood Education), the role of partnership between schools and parents is very crucial in supporting this development. School and parent partnership refers to harmonious and sustainable collaboration between both parties in supporting the process of education and child development. Schools not only function as places for children to learn academically, but also as environments that support their social and emotional development. Teachers in PAUD have the responsibility to create a safe, supportive, and loving learning atmosphere. However, this role cannot be carried out effectively without the support of parents. When parents are actively involved in their children’s education, they not only help childr(Zhang et al., 2024)en understand the importance of learning, but also provide the necessary emotional support. Good communication between parents and teachers helps create consistency between the home and school environments, which is important for children’s emotional stability. Thus, the role of parents and schools in this partnership is not only important for the social emotional development of children, but also to build a strong foundation for their future success. Communities and governments also need to support this effort through policies and programs that facilitate collaboration between schools and families, ensuring that every child has the opportunity to grow and develop optimally. This study analyzes the role of school and parent partnerships in children’s social emotional development. The purpose of this study is to determine the role of school and parent partnerships on children’s social emotional development at PAUD AL-Hidayah, Bug-Bug Village, Lingsar District, West Lombok Regency. The population in the study was 50 PAUD children. Data collection techniques used observation methods, interview methods, documentation methods and questionnaire methods. The data analysis technique used in this study used the product moment correlation statistical technique. Keywords: Partnership, Child Development, Social Emotional.